Streptomyces coelicolor biofilm growth kinetics and oxygen mass transfer within a membrane gradostat bioreactor - De Jager, Debbie (Cape Peninsula University of Technology, 2012)
Thesis (MTech (Chemical Engineering))--Cape Peninsula University of Technology, 2009 === The main purpose of this study was to quantify the growth and oxygen mass transfer kinetic parameters of the filamentous bacterium Streptomyces coelicolor, immobilised on the external surface of a ceramic membrane in a continuously operated pressurised Membrane Gradostat Bioreactor (MGR).